(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Factors affecting customer’s buying decision for small dogs. The population used in the study is the customers who purchased the dog fish market in Ratchaburi. The sample used in the study was from 323 people. There were different tools and methods used during this process. Regression Correlation used to measure the correlation. Firstly, the hypothesis states that different personal factors affect the decision to buy a small dog which this problem is in the medium zone (3.25). The high zone is Search for Information, Evaluation of Alternative , Decision Marking and Post purchase Behavior (4.34, 4.39, 4.35, 4.14). Other personal factor such as gender, age, status, education, estimate salary, family members, different habitats, also affects the decision on buying small dogs. The second assumption of this case study at Fish Market states that the results of the tests using regression showed that the price of the dog was appropriate for its quality, the store is conveniently accessible, and dogs are healthy which have a sig value of 0.030, 0.037 and 0.049.